Al-Quran Mushaf Manuscript A 648 Collection of the National Library of Indonesia: Study of Several Codicological Aspects and Mushaf Texts - Nafisah, Mamluatun (AL QUDS : Jurnal Studi Alquran dan Hadis, 2024)
This study aims to capture the codicological aspects and texts of the ancient Mushaf A. 648 in the collection of the National Library of Indonesia and how the contextualization of these manuscripts is from a historical perspective. In analyzing it, the writer uses a codicological and textological analysis approach. The results showed that Mushaf A 648 in the collection of the National Library of Indonesia was strongly suspected of originating from Aceh. It is not known who copied this manuscript. However, it doesn't seem like an ordinary person. The writing strokes display the art of the beauty of the letters which is quite impressive. In addition, the use of ink in Mushaf A 648 only takes red, black and yellow. For illumination, there is only the beginning and end. The colors red, yellow and black are very dominating with quite detailed and neat processing. The motifs and decorations of Mushaf A. 648 are identical to those of Acehnese decorations. Furthermore, Mushaf A 648 uses 4 tajwid marking systems, namely Â Ø¸ ,ØºÙ†Û ,Ø§Ø¯ØºÙ… ,Ø®. While the rasm used is dominated by rasm imla'i.